Targeted inhibition of CX3CL1 limits podocytes ferroptosis to ameliorate cisplatin-induced acute kidney injury - Qiming Gong; Tengfang Lai; Liudan Liang; Yan Jiang; Fahui Liu (BMC, 2023)
Abstract Background It is widely acknowledged that cisplatin-induced nephrotoxicity hinders its efficacy during clinical therapy. Effective pharmaceutical interventions for cisplatin-induced acute kidney injury (Cis-AKI) are currently lacking. Prior studies have implicated the chemokine CX3CL1 in the development of lipopolysaccharide-induced AKI; however, its specific role in Cis-AKI remains uncertain. This research aimed to comprehensively characterize the therapeutic impact and mechanism of CX3CL1 inhibition on Cis-AKI. Methods This study employed an in vivo Cis-AKI mouse model and in vitro cisplatin-treated podocytes. Kidney pathological changes were assessed using hematoxylin-eosin (HE) and Periodic-Schiff (PAS) staining. Transcriptome changes in mouse kidney tissue post-cisplatin treatment were analyzed through RNA sequencing (RNA-seq) datasets. Evaluation parameters included the expression of inflammatory markers, intracellular free iron levels, ferroptosis-related proteins-solute carrier family 7 member 11 (SLC7A11/XCT) and glutathione peroxidase 4 (GPX4)-as well as lipid peroxidation markers and mitochondrial function proteins. Mitochondrial morphological changes were visualized through transmission electron microscopy. The impact of CX3CL1 on the glucose-regulated protein 78/eukaryotic translation initiation factor 2A/CCAAT enhancer binding protein-homologous protein (GRP78/eIF2α/CHOP) and hypoxia-inducible factor 1-alpha/heme oxygenase-1 (HIF1A/HO-1) pathways in Cis-AKI was assessed via Western Blot and Immunofluorescence experiments, both in vivo and in vitro. Results Kidney CX3CL1 levels were elevated following cisplatin injection in wild-type (WT) mice. Cisplatin-treated CX3CL1-Knockout mice exhibited reduced renal histological changes, lowered blood creatinine (Cre) and blood urea nitrogen (BUN) levels, and decreased expression of inflammatory mediators compared to cisplatin-treated WT mice. RNA-seq analysis revealed the modulation of markers associated with oxidative stress and lipid metabolism related to ferroptosis in the kidneys of mice with Cis-AKI. Both the in vivo Cis-AKI mouse model and in vitro cisplatin-treated podocytes demonstrated that CX3CL1 inhibition could mitigate ferroptosis. This effect was characterized by alleviated intracellular iron overload, malondialdehyde (MDA) content, and reactive oxygen species (ROS) production, alongside increased glutathione/glutathione disulfide ratio, superoxide dismutase (SOD), XCT, and GPX4 activity. CX3CL1 inhibition also ameliorated mitochondrial dysfunction and upregulated expression of mitochondrial biogenesis proteins-uncoupling protein (UCP), mitofusin 2 (Mfn2), and peroxisome proliferators-activated receptor γ coactivator l-alpha (PGC1α)-both in vivo and in vitro. Furthermore, CX3CL1 inhibition attenuated cisplatin-induced endoplasmic reticulum (ER) stress in podocytes. Notably, CX3CL1 inhibition reduced cisplatin-induced expression of HIF-1α and HO-1 in vivo and in vitro. Conclusion Our findings suggest that CX3CL1 inhibition exerts therapeutic effects against Cis-AKI by suppressing podocyte ferroptosis.